(untitled) (The Pakistan Development Review, 2009)
The aim of this study is to analyse the reliability and validity of job factors in relation to the impact of occupational stress on employees’ somatic symptoms, job anxiety and turnover intention through a two time cross-sectional study of the Water and Power Development Authority (WAPDA). The method employed consisted of two times self-reported cross-sectional surveys that covered 420 respondents at T1 and 388 respondents at T2. Results: Appropriate internal consistencies of the seven scales i.e. demands, control, job stress, social supports, employees’ somatic symptoms, job anxiety and turnover intention were obtained. Zero-order correlation and linear and multiple regressions analysis replicated the theoretically assumed structure of the job factors and employees’ somatic symptoms, job anxiety and turnover intention construct in men and women collectively. Evidence of criterion validity was obtained from cross-correlations of the scales and from their linear and multiple regression analysis. Finally, all seven measures were associated with a highly significant ratio of job stress, and the effect was strongest for the job stress ratio as predicted by the fundamental theory of Karasek. Conclusion: We examine how users, who are assimilating job factors into their work, experience the level of work related demands in their jobs, the level of autonomy/control they have over their work, and how these relate to outcomes, such as employees’ somatic symptoms, job anxiety and turnover intention. Based on the results of this study the seven-version scale is considered reliable and serves as a valid instrument for measuring psychosocial pressure in work environment. These outcomes and measures are applicable to all services and manufacturing industries. Keywords: Work Overload, Work Control, Organisational Support, Job Stress, Somatic Symptoms, Job Anxiety, and Employees Turnover Intention (ETI)